Dampak Kualitas Tidur Terhadap Kualitas Hidup Lansia Di Desa Gagak Sipat, Ngemplak, Boyolali - Retna Febri Arifiati; Endang Sri Wahyuni; Putri Utami (Universitas Haji Sumatera Utara, 2023)
Background. The changes experienced by the elderly have an impact on a gradual decline in physical function. The life cycle experienced by the elderly determines the quantity and quality of life and health of the elderly in the future. When compared to young people, the elderly in Indonesia have a 70% to 80% decrease in the effectiveness of their nighttime sleep. Good sleep quality has an impact on the quality of life of the elderly, which can be seen in their effects on physical health, increasing cognitive abilities, concentration, and memory, lowering the risk of falling, and lowering the risk of death. The sleep quality of the elderly can be observed from the preparation for sleeping at night, the quantity of hours of sleep, the factor of sleep depth, the duration of sleep, and the ease of sleeping without medical and pharmacological assistance. Meanwhile, the quality of life of the elderly has a very broad and complex scope because it is interrelated with their level of independence, their social environment, and their physical and psychological health conditions, which can be monitored by the quality of their sleep. Methodology. This study was non-experimental with a cross-sectional analytic survey design. The population of this study was the elderly in the village of Gagak Sipat, Ngemplak Boyolali, with a total of 50 people. The sample selection method uses non-random sampling. The technique used is accidental sampling. Data collection on sleep quality variables used the Pittsburgh Sleep Quality Index (PSQI), and quality of life variables used the WHOQOL-BREF numerical measurement scale, while data analysis used the Chi Square test. Results. The results of the Chi Square test obtained a value of 2 = 12.808 and a p-value of 0.002. Conclusion. The elderly's sleep quality is mostly good, but their life quality is mostly poor, and there is a relationship between the quality of their sleep and the quality of their lives in Gagak Sipat Village, Ngemplak Boyolali, where the better the quality of their sleep, the better the quality of their lives.